We use cookies to personalise content and advertisements and to analyse access to our website. Furthermore, our partners for online advertising receive pseudonymised information about your use of our website. cookie policy and privacy policy.
 
+0  
 
0
65
2
avatar

Let \(f(x) = 2x - 3\) and \(g(f(x)) = 5-4x.\) Find\( g(4).\)

 

Plz help asap. 

Thx in advance

 Aug 18, 2019
 #1
avatar+28134 
+1

g(4) means f(x) = 4, so 2x - 3 = 4 or x = 7/2.

 

Hence g(4) = 5 - 4*7/2  or g(4) = -9

 Aug 18, 2019
 #2
avatar
0

THX SO MUCH. laugh

can you plz help me on this question. That would be amazing . smiley

 https://web2.0calc.com/questions/halp-plz_6

Guest Aug 18, 2019

28 Online Users

avatar
avatar
avatar
avatar